Mechanism of water savings and pollution reduction in paddy fields of three typical areas in southern China - Xiao, Menghua; Li, Yuanyuan; Jia, Yi; Wang, Jianwen (International Journal of Agricultural and Biological Engineering, 2022)
Field irrigation and drainage regulation and fertilization application could affect water utilization and pollution transportation in a paddy field. In this study, representative rice-producing areas of Zhejiang Province in southern China were selected to study the effects of different field water level control (conventional irrigation and drainage W0, controlled irrigation and drainage W1 and W2) and different fertilization methods (2 times of fertilization F2 and three times of fertilization F3) on water irrigation quantity and consumption of rice, rice growth, water utilization, and pollution reduction. Results showed that field water level control had a great effect on irrigation quota in growing period rather than that in soaking period, and irrigation quota for W0 was 37.0%-71.7% higher than that for W1 and W2 in the whole growth period of rice. Although the upper limit of rain storage was greatly increased by W1 and W2, on the contrary, the yield under W1 and W2 was 0.4%-2.1% higher than that under W0. Water consumption, water leakage, and evapotranspiration were 16.63%-34.40%, 39.97%-60.80%, and 9.40%-31.53% lower under W1 and W2 than those under W0, respectively, while it showed no significant changes under W1 and W2. Rainfall use rate and WUEI (water use efficiency of irrigation) under W1 and W2 had been significantly improved by 8.20%-129.58% and 31.58%-201.61% compared to W0. The contribution of nitrogen and phosphorus loss from surface water accounted for 90% and the total pollution load of total nitrogen (TN), NO3−-N, NH4+-N and chemical oxygen demand (COD) were 20.0%-63.4%, 21.8%-66.3%, 21.5%-63.8%, and 21.4%-46.5% lower for W1 and W2 than that for W0, respectively. Meanwhile, compared to F2, dispersed fertilization (F3) was beneficial to increase the yield and decrease pollutant load. Additionally, the path of IRA→NH4+-N→COD and IRA→WCA→WUEI presented partial remediation effect, and the effect size was 23.6% and 38.1%, respectively, the path of IRA→WUEI→WUEET presented a full remediation effect, and the path of IRA→WCA→WUEET presented suppression effect.Keywords: controlled irrigation and drainage, water consumption, water use efficiency, non-point source pollution, structural equation modeDOI: 10.25165/j.ijabe.20221501.6092Citation: Xiao M H, Li Y Y, Jia Y, Wang J W. Mechanism of water savings and pollution reduction in paddy fields of three typical areas in southern China. Int J Agric & Biol Eng, 2022; 15(1): 199–207.